Experimental investigation on H2S and SO2 sulphur poisoning and regeneration of a commercially available Ni-catalyst during methane tri-reforming. (19th January 2021) - Wachter, Philipp; Gaber, Christian; Raic, Juraj; Demuth, Martin; Hochenauer, Christoph
Abstract: H2 S and SO2 poisoning during methane tri-reforming are the main degradation sources for nickel catalysts, especially when exhaust gases are used as reactants. To prolong the lifetime of such applications, it is of primary importance to find strategies which reduce the poisoning effects of sulphur or allow regeneration of poisoned catalysts. The specific feature of tri-reforming, oxygen addition to the reactants, offers possibilities for both of these objectives. This experimental study, based on a specific thermochemical recuperation process, thus scrutinizes three aspects of sulphur poisoning and regeneration during methane tri-reforming focusing on oxygen as key influencing factor: (I) Oxygen addition to the reactants is investigated. (II) A comparison between H2 S and SO2 poisoning is made. (III) Catalyst regeneration by oxygen treatment is performed. The conclusions derived from the results allow significant improvements in terms of catalyst stability and regeneration and thus contribute to expand application possibilities of reforming catalysts. Graphical abstract: Image 1 Highlights: H2 S and SO2 poisoning during methane tri-reforming was executed. Sulphur poisoning experiments on a lab-scale sized test rig were performed. The influence of oxygen on sulphur poisoning was investigated. Catalyst poisoning was reduced by 71% due to the use of oxygen. Full catalyst regeneration by oxygen treatment was achieved within 4.2 h.